Natural disasters characteristic of Georgia - MAIA BLIADZE; SHORENA TKEMALADZE; RUSUDAN TEDORADZE (Research Retrieval and Academic Letters, 2023)
Shovi is a climatic and balneological resort of republican importance in Oni municipality of Racha-Lechkhumi and Kvemo Svaneti region in Georgia. It is located in the valley of the Chanchakhi River (the left tributary of the Rioni River). There were sanatoriums, holiday homes, boarding houses, tourist resorts and others in Shovi. The holiday season lasts from June to October. On August 3, 2023, in Georgia, in Racha-Lechkhumi-Kvemo Svaneti area, near the village of Shov, in the valley of the Bubistskali River, there were natural geological and hydrometeorological events - intense melting of the glacier, precipitation in the form of rain, rock avalanches in the headwaters, landslide-erosive processes and the passage of mudslides - convergence, which led to the formation of an extreme mudflow. The mentioned process was facilitated by the increased air temperature in the recent period, intense melting of glaciers caused by climate change and subsequent atmospheric precipitations. The rocky material and part of the glacial mass that came into the dynamics transformed into a glacial mudflow in the upper part of the valley. In the middle and lower part of the valley, the flow of the river bed washed away the base of the slopes along both slopes and the so-called caused the formation and activation of coastal landslide bodies. 22 , more than 30 people lost their lives in the tragedy. The search for the missing is still ongoing.